Analysis of Comfort Properties of Mulberry Silk and Viscose Blended Knitted Fabrics for Suitability in Temperate Regions - , Shikha Bajaj; , Sandeep Bains (Archives of Current Research International, 2024)
This study reports on the impact of textile properties of knitted fabrics blended with three unlike proportions of mulberry silk and viscose fibre, on desired comfort for temperate regions. An experiment was conducted with knitted textiles, with uneven counts, each of which was mixed with either 60% mulberry silk and 40% viscose, 50% mulberry silk and 50% viscose, or 40% mulberry silk and 60% viscose. As part of the objective evaluation, we evaluated the fabrics on different comfort variables. To achieve the experimental design, thermal conductivity, air permeability, bursting strength and water repellency were taken into account. It has been exercised to bring about a knitted fabric with desired properties in temperate climates. Results suggest that knitted fabrics blended in 60% mulberry silk: 40% viscose in both yarn counts 15 and 20 Nm, were found most suitable for apparel use in temperate regions.These fabrics were holding a good mix of warmth and coolness by having thermal conductivity of 1.140 and 1.145 Clo, air permeability of 439.2 and 435.7 CFM and water repellency of grades 3 for both fabrics. A worthy influence of constructional properties was observed on comfort characteristics. A feeble negative correlation of thermal conductivity with air permeability and water perm was noticed.